Ecologic constituent of risk of reproductive complications - T. A. Golovkova (Kazimierz Wielki University, 2018)
Technogenic pressure contributes to the constant emission of significant amounts of chemical pollutants in the environment, thus increasing the risk of ecologically conditioned pathology in the population of urbanized areas. Of the variety of environmental factors that have a detrimental effect on the body of a future mother, cadmium plays a particularly important role as a risk factor for complications in the course of pregnancy. Therefore, the purpose of the research was to determine the influence of external exposures of cadmium on the level of internal contamination of the body of pregnant women and the frequency of manifestation of nephropathy among residents of Dnipropetrovsk region in the complex impact of different levels of environmental pollution. The research program included an assessment of the cadmium content in life-saving environmental facilities and biological substrates of 89 healthy pregnant women, as well as a retrospective analysis of data of the primary statistical documentation on the complication of pregnancy. It is established that cadmium has a constant presence in environmental objects, in concentrations that do not exceed the normative meanings. The level of cadmium in the blood and urine of women in industrial districts is significantly higher in comparison with the control (p